Iterative Enhancement of Academic Information System UI/UX Through Prototype-Based and User Centered Design Methodology - Vanessa Priscilia Wijaya; Mychael Maoeretz Engel (Komunitas Dosen Indonesia, 2025)
The Academic Information System serves as a core platform for managing academic activities, yet despite it being a core platform there are still many institutions face the same issues related to poor user experience (UX) and user interface (UI) design, which affect the operational efficiency and user satisfaction. While many studies have explored usability improvement in academic systems, few have focused on iterative prototyping combined with user-centered design methodologies in fully deployed university platforms. The goal of this study is to address these issues by redesigning the CIS interface through an iterative, prototype-based using Design Thinking and User-Centered Design (UCD) methodologies. It’s focus on improving system clarity, navigation, and user engagement. Online questionnaires and interviews with 50 students were used to gather data for the primary evaluation, which was based on the User Experience Questionnaire (UEQ). The UEQ was used both before and after the redesign to measure six experiential dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. And the results show significant improvements across all categories with rated excellent, indicating it’s successfully enhanced usability, visual appeal, and workflow clarity. These improvements has made an increased to the user satisfaction during academic task completion. Practically, the redesigned CIS enables students to access critical academic information more efficiently, improving daily academic productivity and digital interaction quality. This study highlights the effectiveness of using iterative, and user-centered methodologies in transforming outdated academic systems into intuitive, human-centered platforms that promote both institutional efficiency and user well-being.